Control of Competing Thermodynamics and Kinetics in Vapor Phase Thin-Film Growth of Nitrides and Borides - Ohkubo, Isao; Aizawa, Takashi; Nakamura, Katsumitsu; Mori, Takao (Frontiers in Chemistry, 2021)
Thin-film growth is a platform technique that allows the preparation of various undeveloped materials and enables the development of novel energy generation devices. Preferred phase formation, control of crystalline orientation and quality, defect concentration, and stoichiometry in thin films are important for obtaining thin films exhibiting desired physical and chemical properties. In particular, the control of crystalline phase formation by utilizing thin-film technology favors the preparation of undeveloped materials. In this study, thin-film growth of transition metal nitride and rare-earth metal boride was performed using remote-plasma-assisted molecular beam epitaxy and hybrid physical–chemical vapor deposition techniques, and was successfully achieved by tuning the competition between thermodynamics and kinetics during vapor-phase thin-film growth. Growth conditions of high crystalline quality titanium nitride thin films and high phase purity ytterbium boride thin films were not thermodynamically favorable conditions. Appropriate control of the contribution degree of thermodynamics and kinetics during vapor-phase thin-film growth is crucial for fabricating high phase purity and high crystalline quality thin films.